KERAGAMAN GENETIK BULU BABI TRIPNEUTES GRATILLA (LINNAEUS, 1758) DI PERAIRAN PANTAI DESA LAMBAKARA, SUMBA TIMUR, NUSA TENGGARA TIMUR (NTT) - Nomleni, Aryok; Turnip, Gilbert; Adin Afandi, Lutfi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
A total of 14 samples were taken from the coastal waters of East Sumba. The sample was isolated from genomic DNA using the KIT GENE AID method using GO TAQ Green PCR Mix material and universal primer pairs LCO1490 and HCO2198 to determine the expression of the amplified COI gene (PCR). The PCR results were sent to First Base CO (Malaysia) for sequencing. The sequence length of the COI gene sequencing of the genus Tripneustes from NTT waters using universal primers LCO1490 and HCO2198 was 690-700 bp. The results showed that the genetic diversity of the sea urchin population in the coastal waters of Sumba was 0.83516 while the value of nucleotide diversity was 0.00516. The total genetic distance ranged from 0.000-0.010. All population genetic distances are still relatively low because genetic distances less than 0.010-0.099 are included in the low category. This close genetic distance causes connectivity between the two populations because there is gene flow. Based on the phylogenetic analysis, it was found that the populations in Sumba waters and some areas (outgroups) were genetically close